Rural Land Use in China - Wang, Yongsheng; Wen, Qi; Ge, Dazhuan; Zhang, Bangbang (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Land use is the projection of human activities in space, and it has become an important insight into the transformation and reconstruction of human society and economy. Rural land use in China is undergoing rapid transformation driven by the rapid development of science and technology. Effectively grasping the change and transformation process of rural land use and its internal mechanism provides an important reference for revealing the inherent laws of China's rural development. Rural land use is closely related to the rural vitalization strategy and urban-rural integration in the new era. An in-depth study of China's rural land use and policy reform provides the basis of knowledge for formulating and optimizing urban-rural relations. This Special Issue focuses on the changes, effects, and regulation of rural land use in China, focusing on its main contradictions and solutions, building a cooperative network and sharing platform for rural land use research from a multidisciplinary perspective, and further deepening the theoretical innovation and practical application of rural land use research. We invited scholars from various disciplines to contribute to the Special Issue, especially with papers on the subjects of theoretical innovation, technological innovation, and practical innovation in this field.